Anti‐GM‐CSF therapy in psoriasis. (1st June 2019) - Papp, K.A.; Gooderham, M.; Jenkins, R.; Vender, R.; Szepietowski, J.C.; Wagner, T.; Hunt, B.; Souberbielle, B.; ,
Summary: Psoriasis is a long‐lasting disease involving inflammation of the skin. In the most common form of this disease ‐ plaque psoriasis ‐ the inflammation is visible as raised, reddened and often scaly areas which may extend widely over the body. Although not generally a life‐threatening condition, psoriasis may increase the risk of other serious disorders (such as cardiovascular disease), and often leads to much reduced quality of life for patients ‐ through physical discomfort (itching, pain), disability, and related emotional trauma. Furthermore, psoriasis occurs worldwide (affecting up to 3% of the populations in various countries) and cannot be completely cured by available treatments. Together, these issues make the disease a serious global burden. Granulocyte‐Macrophage Colony‐Stimulating Factor (GM‐CSF) is made in the body and is important in controlling functions of the body's immune system and the processes involved in inflammation. Therefore, this study was carried out to establish whether blocking the activities of GM‐CSF in patients with moderate or severe plaque psoriasis could result in significant improvement of the disease. In total, 122 patients were enrolled from Canada, Denmark, Germany, Latvia and Poland. The patients were treated over 10 weeks either with namilumab (GM‐CSF blocker) or a placebo (inactive): assessments of their psoriasis were made during this period, and completed after an additional 2 weeks. Notably, throughout the 12‐week study duration no significant improvement was detected for namilumab‐treated patients ‐ in marked contrast to treatment benefit found in a similar study involving patients with rheumatoid arthritis. These findings point to different roles for GM‐CSF in the two diseases, and suggest that blocking GM‐CSF activity alone is not enough for effective treatment of plaque psoriasis.